Natural Resource Planning and Recreation Opportunity Model for Jeram Linang Forest Recreation Area. - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract Leisure and outdoors recreation opportunity is becoming an important lifestyle for Malaysians. The major factors affecting this lifestyle are population increase, better income, more leisure time and ease of mobility has increased the demand for outdoors recreation. As a result of these increases, more natural recreation areas are being patronized by the population. Jeram Linang Forest Recreation Area in Machang, Kelantan is one of such areas. The presence of hundreds of visitors during weekends and holiday vacations has resulted in environmental degradation, overcrowding, vandalism, noise and water pollution. A study to address these issues was conducted by proposing a natural resource planning and recreation opportunity model. This model was proposed based on a survey and observation of the visitors’ activities and their impact on the area. Recommendations and proposals on environmental quality management will be proposed. This paper will discuss the stages of the model